Geography rules too!: Economic development and the geography of institutions - E. Maarten Bosker; Harry Garretsen (Center for Economic Studies and ifo Institute (CESifo), 2006)
To explain cross-country income differences, research has recently focused on the so-called deep determinants of economic development, notably institutions and geography. This paper sheds a different light on these determinants. We use spatial econometrics to analyse the importance of the geography of institutions. We show that it is not only absolute geography, in terms of for instance climate, but also relative geography, the spatial linkages between countries, that matters for a country's gdp per capita. Apart from a country's own institutions, institutions in neighboring countries turn out to be relevant as well. This finding is robust to various alternative specifications.
Keywords: O11; F43; 330